Grenada Education Management Information System - Porta, Emilio (World Bank, Washington, DC, 2017)
The Education Management Information System (EMIS) country report for Grenada includes the following headings: background which includes education data in Grenada, EMIS staff, facilities and equipment, EMIS data, and publications; prerequisites of quality; assurances of integrity; methodological soundness; accuracy and reliability; serviceability; and accessibility.